Unbundling the effects of institutions on firm resources: The contingent value of being local in emerging economy private equity. (4th September 2014) - Taussig, Markus; Delios, Andrew
<x xml:space="preserve">Abstract</x> How do host country institutions influence the value of a firm's local resources? Using a novel dataset on the performance of 47 private equity (PE) firms in 49 emerging economies, we show evidence that the answer depends on the type of institution. Focusing on conditions at the time of initial investment, we find that PE firms with local origins and foreign PE firms with local experience performed better when contract enforcement institutions were weak than when they were strong. Financial development, in contrast, may have undermined the value of PE firm local origins. These results help reconcile contrasting findings on how host country institutions influence performance and lead us to contend that unbundling institutions is necessary for continued development of the institutions‐based view. Copyright © 2014 John Wiley & Sons, Ltd.